Focal lymphovascular space invasion: Friend or foe? A large retrospective analysis on stage I endometrioid endometrial carcinomas - Capasso, Ilaria; Perrone, Emanuele; Loverro, Matteo; Giannarelli, Diana; Nero, Camilla; Tortorella, Lucia; Esposito, Giovanni; Palmieri, Emilia; Zannoni, Gian Franco; Santoro, Angela; Salvati, Fabiana; Pirrelli, Fulvia; et al. (European journal of cancer (1990), 2025)
Literature is inconsistent with respect to clinical value of lymphovascular space invasion (LVSI) semiquantitative assessment. We aim to investigate the prognostic role of LVSI extent in stage I endometrioid endometrial carcinomas (ECs) classified by immunohistochemistry (IHC) analysis. Patients with stage I endometrioid EC undergone primary surgery were retrospectively included. Following World Health Organization definition for LVSI pathologic evaluation, subjects were divided into: LVSI-negative; LVSI-focal; LVSI-substantial. An IHC-based model was utilized to classify patients into: p53-aberrant (p53abn); mismatch repair deficient (MMRd); mismatch repair proficient with positive estrogen receptors (MMRp-ERpos); and mismatch repair proficient with negative estrogen receptors (MMRp-ERneg). 2091 subjects were included and divided into: 78.0 % (n:1631) LVSI-negative, 10.6 % (n:221) LVSI-focal, and 11.4 % (n:239) LVSI-substantial. Presence of LVSI (any extent) was associated with older age, larger tumor size and deeper myometrial infiltration. Patients with LVSI-substantial presented with higher incidence of grade 3 tumors, p53abn and MMRd status. Conversely, most LVSI-negative and LVSI-focal cases were MMRp-ERpos. At multivariable regression, LVSI-substantial was independently associated with reduced 5-year disease-free survival (DFS) and overall-survival (OS). LVSI-negative and LVSI-focal groups had similar DFS (p = 0.42) and OS (p = 0.09), whereas comparison with LVSI-substantial demonstrated significantly poorer outcomes for patients with substantial invasion. These findings were confirmed in sub-analyses of cases with grade 1–2 endometrioid and myometrial infiltration, and in the MMRp-ERpos cohort. In stage I endometrioid ECs, LVSI-focal was not associated with reduced oncologic outcomes compared to LVSI-negative. In contrast, LVSI-substantial was associated with aggressive clinicopathologic and molecular features and behaved as an independent prognostic factor for reduced survival. Our results were further confirmed in two low-risk EC settings: grade 1–2 with myometrial infiltration, and the MMRp-ERpos group. •Inconsistencies persist on the prognostic value of focal LVSI in stage I ECs.•Stage I endometrioid ECs with focal and negative LVSI have similar prognosis.•In contrast, endometrioid ECs with substantial LVSI had worse survival outcomes.•Sub-group analyses of ECs with very low-risk features confirmed these results.